Seismic monitoring network and earthquake hazard mitigation - Shah, Mohammad Daud; Qaisar, Mohammad; Mahmood, Tariq (Journal of Himalayan Earth Sciences, 2002)
Pakistan Atomic Energy Commission (PAEC) is operating a seismic monitoring network since 1975 and recently installed a 24-bit digital seismograph network of four stations to improve the quality of the seismic data, seismic event detection and location capability. The high quality seismic data now available to the scientists will be very helpful to understand the earthquake source process, earth structure and seismotectonics of the region. The accurate location of seismic event will help in providing the immediate emergency relief in the affected areas.